Factors that Influence the Formation of Public Stigma Towards Leprosy Sufferers in East Kolaka Regency - Kaharuddin, Kaharuddin; Tasnim, Tasnim; Amraeni, Yunita; Hariadhin Depu, Anry (Magister Kesehatan Universitas Mandala Waluya, 2024)
Introduction:Leprosy can cause health problems in the form of permanent disability. Disability due to leprosy is not only physical which has an impact on daily activities and social participation, but also economic and psychological. The stigma of society towards leprosy sufferers can cause negative feelings of leprosy sufferers such as being embarrassed to socialize with the surrounding community to isolating themselves. The purpose of this study was to see the factors that influence the formation of public stigma towards leprosy sufferers in East Kolaka Regency. Method:This study uses a qualitative descriptive approach with an exploratory research type by conducting direct observation and in-depth interviews. The subjects were all people in Ladongi District and Aere District, East Kolaka Regency, the determination of informants in this study was carried out through purposive sampling techniques. Result:Factors that influence the stigma of society towards leprosy in Kolaka Regency occur due to the lack of public knowledge regarding leprosy, the existence of a culture and tradition of society that avoids or even labels leprosy sufferers with negative things, public concerns about the transmission of leprosy when they are close to or live side by side with leprosy sufferers, and the influence of religion and community beliefs that consider leprosy sufferers as a punishment from God for the sins they have committed. Conclusion: Leprosy sufferers need support from the community and family, so that they have the confidence to undergo treatment, thereby reducing the prevalence of leprosy in East Kolaka Regency.